2018
DOI: 10.1111/nin.12274
|View full text |Cite
|
Sign up to set email alerts
|

Bad news: Families’ experiences and feelings surrounding the diagnosis of Zika‐related microcephaly

Abstract: The rapidly increasing number of cases of Zika virus and limited understanding of its congenital sequelae (e.g., microcephaly) led to stories of fear and uncertainty across social media and other mass communication networks. In this study, we used techniques generic to netnography, a form of ethnography, using Internet‐based computer‐mediated communications as a source of data to understand the experience and perceptions of families with infants diagnosed with Zika‐related microcephaly. We screened 27 YouTube™… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 37 publications
1
27
0
9
Order By: Relevance
“…Prior research found that vector-borne viruses cause not only clinical malaise but also emotional symptoms; as an example, 50% of individuals diagnosed with Chikungunya perceived that it affected their emotional state [ 16 ]. In line with other studies, we found that feelings of pain, sadness, and hopelessness, guided by uncertainties about the child’s health and lack of healthcare professionals’ clarity, lead to poor mental health outcomes, anxiety, worry, depression, and stress [ 27 ]. During pregnancy, negative perceptions about ZIKV and possible consequences on children’s health were similar for both groups of women, and long-term implications of maternal health outcomes were present in families with microcephalic infants [ 25 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Prior research found that vector-borne viruses cause not only clinical malaise but also emotional symptoms; as an example, 50% of individuals diagnosed with Chikungunya perceived that it affected their emotional state [ 16 ]. In line with other studies, we found that feelings of pain, sadness, and hopelessness, guided by uncertainties about the child’s health and lack of healthcare professionals’ clarity, lead to poor mental health outcomes, anxiety, worry, depression, and stress [ 27 ]. During pregnancy, negative perceptions about ZIKV and possible consequences on children’s health were similar for both groups of women, and long-term implications of maternal health outcomes were present in families with microcephalic infants [ 25 ].…”
Section: Discussionsupporting
confidence: 89%
“…Only a few studies have explored mental health outcomes and the emotional state of women exposed to ZIKV in families carrying ZIKV-associated microcephalic children [ 13 , 24 , 25 , 26 , 27 , 28 ], all of them were performed in Brazil. There was one cross-sectional study where stress, anxiety, and depression were reported from 163 caregivers of children with microcephaly vs. 324 caregivers of healthy children [ 13 ]; another cross-sectional survey study with 50 caregivers of affected children without a comparison group [ 28 ]; and only one qualitative study based on participant observations [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies did not specify the age of the affected children, but it was inferred that these satisfied the inclusion criteria because of the references to ‘infants’, parental experience of swallowing difficulties in the first days and weeks, and the use of health services for diagnosis and management of microcephaly. Two studies focused on parents and family (n = 23), principally mothers, either using focus groups to collect data,[ 30 ] or analysing parents’ YouTube videos depicting their experience[ 31 ]. Two studies, one focusing on mothers of children with Zika-related microcephaly (n = 12)[ 32 ] and one on fathers of these children (n = 5)[ 33 ], employed interviews alone.…”
Section: Resultsmentioning
confidence: 99%
“…All but one study[ 34 ] presented a clear question; all studies had a qualitative design and used appropriate methodology, but with a moderate risk of bias in reported recruitment, data collection and analysis strategies in some studies. Two studies did not report clear findings[ 31 , 34 ]. However, these two studies were the only ones to address the relationships between researchers and participants (reflexivity)[ 31 , 34 ].…”
Section: Resultsmentioning
confidence: 99%